MODERN METHODS FOR PRODUCING Β-GALACTOSIDASE - Svetlana Andreevna Ryabtseva; Andrew Aleksandrovich Skripnyuk (Наука. Инновации. Технологии)
This article discusses various methods for obtaining and identify several key areas for improving β-galactosidase technology.